Олимпизм в аспекте философии жизни - Косяк, В.; Kosyak, V. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Проблема исследования – осмысление аргументации сближений олимпизма и философии жизни. Акту-альная цель – попытка эксплицирования олимпизма и спорта в целом в парадигме философии жизни. Автор Обосновывается положение о том, что генезис современного олимпизма стал возможным благодаря философии жизни, установки которой (получение радости от жизни, денотативность тела, культивиро¬вание лучшего типа человека, почитание аристократизма и сильной личности, презрение к декадансу) с энтузиазмом были восприняты идеологом олимпизма бароном Пьером де Кубертеном. Философия олимпизма и философия жизни противопоставляют сциентизму холизм, иррациональность, непосредственность самой жизни, максимум которой понимается как высшая ценность. Концептуальными атрибутами, общими для философии жизни, философии олимпизма и спорта в целом, автор называет свободу воли, антисциентизм, чувственное (те¬лесное) знание, витализм, эстетизм, телоцентризм. The problem of research – understanding the arguments of the rapprochement of the Olympism and the philosophy of life. Current goal – an attempt to explicate Olympism and sport in general in the paradigm of the philosophy of life. The author proves the opinion that the genesis of the modern Olympism became possible due to the philosophy of life, the ideas of which (the joy of life, denotative of the body, the cultivation of a better type of man, respect of aristocracy and a strong personality, contempt for decadence) were enthusiastically received by baron Pierre de Kuberten, the ideologist of Olympism. The philosophy of Olympism and the philosophy of life contrapose scientism to holism, irrationality, spontaneity of life itself, the maximum of which is understood as the highest value. By author, conceptual attributes that are common to the philosophy of life, the philosophy of Olympism and sport in general, are the freedom of the will, anti-scientism, sensory knowledge, vitalism, aestheticism, centrism of the body.
Olympism in the Aspect of the Philosophy of Life
Keywords: олимпизм; философия жизни; холизм; максимум жизни; антисциентизм; витализм; эстетизм; телоцентризм; Olympism; the philosophy of life; holism; the maximum of life; antiscientism; vitalism; aestheticism; centrism of the body; 796:101